Relationship between occlusion and dental attrition in a group of young Polish adults - Grzegocka, Kinga; Williams, Stephen; Loster, Jolanta; Wieczorek, Aneta; Loster, Bartłomiej (Journal of Stomatology, 2016)
Aim of the study. To identify dental attrition in a group of young adults selected irrespective of occlusion. Classification of dental attrition was proposed and used to relate attrition to the type of occlusion observed simultaneously considering the subjective indication for orthodontic treatment as estimated by the evidence-based method derived by the Danish Ministry of Health. Materials and methods. The study material consisted of 250 plaster casts (69 males, and 181 females, average age 18y 9m, max 20y 9m, min 16y 10m), included in the study irrespective of the type of occlusion they exhibited. All models were examined by one author (K.G.) recording molar and canine relationship, Angle’s classification, maximum overjet and overbite, cingulum contact, midline shift, cross bite, scissors bite and open bite. Attrition was recorded using a classification assessing six tooth groups (maxillary/mandibular incisors, maxillary/mandibular canines, maxillary/mandibular buccal teeth) and three surfaces (incisal or occlusal, facial or buccal, palatal or lingual). A score system was developed and the tooth in each group seen to be most worn was selected to represent the segment. Results. 129 individuals (51.6%) manifested dental attrition (38 males, 91 females). The most affected were incisal surfaces of maxillary and mandibular canines and incisal surface of mandibular incisors. The statistic analysis showed a higher attrition incidence in patients with forced bite and Class II div 2 malocclusion. Conclusions. The study demonstrates a high prevalence of dental wear in Polish young adults, especially in forced bite and Class II div 2 malocclusion. The risk of tooth wear should be considered as a valid reason to offer orthodontic treatment.